2014
DOI: 10.1172/jci75894
|View full text |Cite
|
Sign up to set email alerts
|

HIV-specific humoral responses benefit from stronger prime in phase Ib clinical trial

Abstract: BACKGROUND. Vector prime-boost immunization strategies induce strong cellular and humoral immune responses. We examined the priming dose and administration order of heterologous vectors in HIV Vaccine Trials Network 078 (HVTN 078), a randomized, double-blind phase Ib clinical trial to evaluate the safety and immunogenicity of heterologous prime-boost regimens, with a New York vaccinia HIV clade B (NYVAC-B) vaccine and a recombinant adenovirus 5-vectored (rAd5-vectored) vaccine. METHODS.NYVAC-B included HIV-1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…Furthermore, a DNA-C prime (two plasmid vectors)/NYVAC-C (vP2010; old single-component) boost immunization protocol tested in a phase I clinical trial (EV02) resulted in significantly enhanced HIV-1-specific T-and B-cell immune responses (25), though again with an Env antigen-specific bias that was polyfunctional and long-lasting (13). In another recent human clinical trial (HVTN078), NYVAC was used in combination with an adenovirus 5 (Ad5)-based HIV vaccine, and it was shown that NYVAC was a potent boosting component (23). A similar NYVAC-based HIV/AIDS therapeutic vaccine candidate expressing Env and Gag-Pol-Nef HIV-1 antigens from clade B (NYVAC-B) has been evaluated in HIV-1-infected patients on antiretroviral therapy in a phase I clinical trial (Theravac-01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a DNA-C prime (two plasmid vectors)/NYVAC-C (vP2010; old single-component) boost immunization protocol tested in a phase I clinical trial (EV02) resulted in significantly enhanced HIV-1-specific T-and B-cell immune responses (25), though again with an Env antigen-specific bias that was polyfunctional and long-lasting (13). In another recent human clinical trial (HVTN078), NYVAC was used in combination with an adenovirus 5 (Ad5)-based HIV vaccine, and it was shown that NYVAC was a potent boosting component (23). A similar NYVAC-based HIV/AIDS therapeutic vaccine candidate expressing Env and Gag-Pol-Nef HIV-1 antigens from clade B (NYVAC-B) has been evaluated in HIV-1-infected patients on antiretroviral therapy in a phase I clinical trial (Theravac-01).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recombinant NYVAC vectors expressing HIV-1 Env, Gag, Pol, and Nef antigens from clade B or C elicited strong, broad, and polyfunctional T-cell immune responses in mice, nonhuman primates, and humans, together with varied levels of humoral re-sponses against HIV-1 gp120 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)). An additional feature is that the current NYVAC vectors preferentially trigger CD4 ϩ T-cell responses (13,14,24,25) in both humans and macaques, inferring immunologically the recruitment of stronger B-cell responses than ALVAC-based vectors.…”
mentioning
confidence: 99%
“…The attenuated poxvirus strain NYVAC (New York vaccinia virus) has been used as a vaccine vector in HIV clinical trials (3,4). Studies in nonhuman primates showed that NYVAC expressing Env and/or the Gag-Pol-Nef (GPN) clade C HIV antigens elicited a balanced CD4/CD8 T cell response (5) or robust T cell immunity (6).…”
mentioning
confidence: 99%
“…Clinical trials with homologous NYVAC vectors expressing HIV-1 antigens (gp120 Env and the polyprotein Gag-Pol-Nef) have shown a limited immunogenicity profile with a preference for CD4 ϩ T cell activation, which was markedly enhanced when priming was performed with a DNA vector expressing the same HIV-1 antigens (29)(30)(31)(32)(33). Thus, in order to optimize the immunization protocol with NYVAC vectors expressing HIV-1 antigens, various approaches in NHPs have been evaluated, either comparing NYVAC to ALVAC (13) or combining NYVAC with DNA vectors (10), peptides (22), and dendritic cell targets (28), which have all demonstrated promising results.…”
mentioning
confidence: 99%